FUNGSI PENGAWASAN KEPALA SEKOLAH DAN DISIPLIN KERJA GURU SERTA PENGARUHNYA TERHADAP EFEKTIVITAS PROSES PEMBELAJARAN - Ujang Safii (Universitas Wiralodra, 2021)
Abstract In achieving the effectiveness of the learning process, the teacher plays an important role. Namely teachers who have high work discipline with the support of supervision from their leaders. Therefore, the purpose of this study among others is to analyze the effect of the supervisory function on schools and the work discipline of teachers both individually and multiple. The research method used is descriptive and verification methods, with data collection techniques using a Likert scale questionnaire, against 55 teachers. Processing of research results using regression analysis techniques. The significance test uses the F-test. The results showed that: (1) There was an influence of the principal's supervisory function on the effectiveness of the learning process. (2) There is an influence of teacher's work discipline on the effectiveness of the learning process. (3) There is an influence of the principal's supervisory function and the simultaneously working discipline of the teacher on the effectiveness of the learning process. The author suggests that: (1) The results of this study have proven the influence of the principal's supervisory function on the effectiveness of the learning process. So to maximize the effectiveness of the learning process can be done by improving several dimensions of supervision that tend not to be optimal, especially regarding routine inspections (regular), evaluation of the implementation of supervision and reporting systems both verbally and in writing. (2) From the results of the analysis it is evident that in general the teacher's work discipline is already good, but in order to improve the effectiveness of learning there is still something that needs to be developed in terms of work discipline especially concerning leadership, inherent supervision and remuneration. Can be done with enlightenment at the meeting as a vehicle for socialization and the benefits of the rules. More than that, the rewards for job performance should be adjusted to the conditions of today's employee needs. With a balanced reward the teacher realizes that work is more disciplined. So the effectiveness increases better.